Assessing optoelectronic properties of PbI2 monolayer under uniaxial strain from first principles calculations. (June 2019) - Hoat, D.M.; Vu, Tuan V.; Obeid, Mohammed M.; Jappor, Hamad R.
Abstract: In this work, the effect of vertical uniaxial strain on the electronic and optical properties of PbI2 monolayer was investigated by means of the first-principles calculations with full-potential linearized augmented plane-wave (FP-LAPW) method. The strain is applied by varying the thickness of monolayer. Our calculations asserted that unstrained PbI2 monolayer has a wide indirect band gap of 2.476 eV. The valence band and conduction band are mainly dominated by the I- 5p and Pb- 6p states, respectively. The band gap increases as the strains go from −12% to 12%, but this parameter shows a higher dependence on the compressive strain than on the tensile strain. Also, the optical properties of PbI2 monolayer depend strongly on the applied strain, especially in the low energy range up to deep ultraviolet. Interestingly, while the compressive strains decrease the band gap and the absorption coefficient of considered material, they can widen the absorption band, that is the capability of PbI2 monolayer of absorbing a wider range of light. Highlights: Strain effect on the electronic and optical properties of PbI2 monolayer is systematically studied. PbI2 is a wide band gap semiconductor and its band gap value increases with increasing the strain value. Changing trend of band gap is attributed to the interaction between Pb-6p and I-5p states. Optical properties also strongly depend on the applied strain. Compressive strains can widen the absorption band of PbI2 monolayer.